1995
DOI: 10.1111/j.1439-0434.1995.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Crop Growth, Disease and Yield Components of Rusted Phaseolus Beans in Ethiopia

Abstract: Crop growth and disease epidemics in sprayed and non‐sprayed bean plots, artificially infected with rust (Uromyces appendiculatus) 3 weeks after emergence. were assessed weekly in two cultivars, at two locations for two seasons. Disease intensity was regulated by the application of a fungicide at 5 spray frequencies. Fungicide application influenced leaf area index (LAI) and reduced rust intensity. The fungicide had no significant effect on other diseases and dead leaf area. Fungicide application increased see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This relationship was seen from early pod formation (41 DAP) but became stronger with time, which implies that leaf area duration was particularly important in conferring a large yield. Similar results were obtained by Hatbu & Zadoks (1995) and Berrocal-Ibarra et al (2002) working with common bean and have also been reported in soybean (Kumudini et al 2001;Kumudini 2002;Takahashi et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…This relationship was seen from early pod formation (41 DAP) but became stronger with time, which implies that leaf area duration was particularly important in conferring a large yield. Similar results were obtained by Hatbu & Zadoks (1995) and Berrocal-Ibarra et al (2002) working with common bean and have also been reported in soybean (Kumudini et al 2001;Kumudini 2002;Takahashi et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Such data can be generated through sequential analysis, a quantitative scrutiny of events by means of cross-sectional and longitudinal studies (Zadoks, 1972;1978). This approach has been effectively used in establishing relationships between disease, crop growth, yield and yield components in the bean rust pathosystem (Habtu & Zadoks, 1995;Habtu et al,1997).…”
Section: Introductionmentioning
confidence: 99%
“…Crous & Braun] of dry beans in Tanzania, Mongi et al (2018) demonstrated that the yield components of various treatments were strongly influenced by the amount of rain received during the growing season because of its influence on disease development. Habtu and Zadoks (1995) speculated that the effect of bean rust [Uromyces appendiculatus (Pers.) Link] on yield components varied with climatic conditions, cultivars, and the host-parasite interaction.…”
Section: Discussionmentioning
confidence: 99%